Vpliv izbranih testov moči na rezultat teka na 60 m pri mlajših atletih - Kreft, Robi (Šport (Ljubljana), 2017)
The purpose of the research was to determine the effect of selected strength tests onthe running the 60m sprint for young athletes aged 9 to 13 years. In a sample of test takers were included 57 young athletes, in which the youngest was 9 years old and the oldest 13 years old. All young athletes involved in the training process in their athletic clubs. The sample of predictors variables have been included following strength tests: the standing long jump and the standing triple jump, vertical jump with a counter movement (CMJ) and five consecutive vertical jumps over obstacles. According to the results of the regression analysis in the category of young athletes U12 there is a significant correlation between the multiple running at 60 m and the set of predictors (R = .86). A statistically significant predictor of the individual is the standing long jump. In the category of young athletes U14, there is also significant multiple connection running at 60 m with a strenght test (R = 0.85). But we can not identify any individual characteristic connection strength test with a score sprint to 60 m. Near the statistical significance of the test is two legged vertical jumping over 5 obstacles.
Keywords: athletics; atletika; mlajši atleti; moč; sport; sprint 60m; strength; šport; tek na 60 m; younger athletes